Satisfação da equipe de enfermagem do serviço de atendimento móvel às urgências (SAMU) no ambiente de trabalho - Campos, Renata Moreira (2005)
Descriptive exploratory study, prospective with quantitative approach, performed on the Medical Regulation Central of SAMU/Natal, aiming to identify the level of professional satisfaction of the members of the nursing team working at SAMU/Natal; and verify the degree of importance attributed by the professionals to each of the components Professional Satisfaction: autonomy, interaction, professional status , work requirements, organizational rules and remuneration. The population was of 60 professionals, with data collected from january to february 2005. We used an instrument translated and validated by Lino (1999) to the portuguese language, the Professional Satisfaction Rate (PSR). The results demonstrate that there was a slight predominance of the female gender (54,9%); aged between 36 and 45 years old (60,8%); married (58,8%), 82,4% with children, 30,8% aged between 05 and 09. Regarding formation, we observed that 78,4% were nursing technicians and 21,6% nurses, formed for 11 to 15 years (17,5%). From the 11 nurses, 09 (81,8%) informed they have specialization, 29,4% of the team has been working for 11 to 15 years on the urgency area, 58.8% works for more than 02 years on SAMU, 72,6% of the team members have fixed work schedules. There was homogeneity on the work shifts: 41,2% on the day shift and 53% on the night shift. Regarding the reason to be working on SAMU, 64% chose to work in the service, and among these 76,3% predominantly perform direct care to the patients, 96,1% like and are satisfied to work in the service. Regarding the remuneration, 90,9% informed they receive 05 to 10 minimum wages; 70% of the technicians informed they receive -2 to 05 minumum wages, 50,1% informed they receive no additional benefit. The analysis of PSR through Cronbach s Alpha Coeficient resulted on the value of 0,94 and through Kendall s Tau Coeficient on 0,87, demonstrating to be a trustworthy instrument to measure the level of professional satisfaction of the SAMU nursing team, in our environment. As for the level of importance attributed to the components of professional satisfaction, we indentified that the nursing team considered the Autonomy component as the most important, followed by the component Remuneration, Interaction, Work Requirements, Work Requirements, Organizational Rules and Professional Status . Regarding the current level of professional satisfaction, we identified they were most satisfied with the Professional Status , Autonomy, Interaction, Remuneration, Work Requirements and Organizational Rules. The real professional satisfaction level, calculated through statistics, however, tells these professionals are more satisfied with Autonomy, Remuneration, Interaction, Work Requirements, professional Status and Organizational Rules. The PSR in our work was of 8,6, indicating the SAMU Natal nursing team has little satisfaction on their work environment